(3bQGAI bGdhf hGdOhQis - (3YKeGf Hf YeQ Hf CHj HcQ GdfGTQj, Yaja GdOjf , J (B848 (3g`s
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B: (3GdMeO ddg MeOkG jhGai fYeg hjcGaF eRjOg hbO ESJNQJ Gddg JYGdi hCedjJ gPg GdhQjbGJ ai ePgH bGdhf hGdOhQi , hPcQJ dcd hGMO efgeG WQjbI hGMOI s
(3BNQgG (B:s
(3Gddge CLYd GdbQBf MLI dfG , hdG JLYdg MLI YdjfG bGd eDdagG CcedJ JNQjLgG ai eOjfI RHjO JeJ hHGdNjQ YeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3cJHJ HYV GdYfhGfGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG EWGQGJ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs